Firm's Resources and Firm's Performance of Indonesian Manufacturing Firms: The Role of Emerging Market and Firm Characteristics - Ellitan, Lena (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
The broad objective of this study is to investigate the effects of firm's resources on performance. The specific objectives are as follows: (1) to investigate relationship between firm resources and firm performance (2) to investigate relationship between firm resources and firm growth (3) to analyze sensitivity of the resource-growth (4) to analyze sensitivity of the resource-performance (5) to examine inter-relationship between performance and growth. This study is expected to contribute to the theory and practice in strategic management, operation management, and resource-based theory, particularly in the Indonesian manufacturing sector. It attempts to provide a framework for managing the resources and the policies, in organizations by developing practical guidelines for practitioners.